Scientific evaluation of the properties of mangrove ecosystems and their role in mitigating the intensification of the greenhouse effect - Alves, Arielly Nara; Barrraqui, Nataly (Brazilian Journal of Production Engineering, 2024)
There are various greenhouse gases in the atmosphere that radiate across the Earth's surface. As this worsens, the global warming process begins. The aim is to find a way of mitigating the effects through environmental preservation and to demonstrate the socio-economic value of mangroves, which contribute to their ability to catalyze gases that aggravate the greenhouse effect by absorbing and storing a portion of carbon dioxide (CO2); The methodology of this article aims to review the literature using the Procknow-C method and obtain data on the plant morphology of mangroves in two regions of the municipality of Vitória, Espírito Santo, in order to carry out a comparative analysis between the means chosen for counting stomata. This showed how the mangrove ecosystem contributes to the preservation of existing biodiversity, demonstrating a socio-economic and cultural role, and in digital trend markets. In conclusion, the climate stability generated by mangroves is due to the properties of microorganisms and the ability of species to absorb greenhouse gases (GHG). However, in an area where pollution is high, the species will not be able to absorb significantly. On the other hand, when there is degradation and deforestation, this carbon is released, resulting in potentially high greenhouse gas emissions.
Keywords: Mangrove; Ecosystem; Carbon; Climate changes; ProKnow-C